Improved light absorption enables highly efficient carbon dots luminescent solar concentrator - Lin, Jishuai; Wang, Lihua; Meng, Xiangyong; Li, Weihua; Ren, Nan; Tao, Lin; Xiao, Junlong; Jing, Qiang; Song, Yang; Zhao, Haiguang (Applied physics letters, 2025)
Carbon dots (CDs) offer several advantages, including non-toxicity, facile synthesis, high fluorescence efficiency, and large Stokes shift, rendering them up-and-coming candidates for luminescent solar concentrators (LSCs). However, the inherently weak light absorption of CDs significantly hinders LSC performance. Here, by modifying the space-confined vacuum heating method, we synthesized high quantum yield CDs with increased size and improved absorption cross section (up to 2.7 times greater than the smaller counterparts), which was elucidated by the size-dominated non-resonant absorption mechanism. The enhanced absorptivity at reduced concentration was demonstrated to mitigate aggregation-induced quenching effectively. Furthermore, we designed a multi-film coating structure to block and recycle the transmitted harmful ultraviolet and short-wavelength blue light through optical interference, thereby fully exploiting this ‘useless’ waveband. By optimizing both the CD absorption cross section and the blue light recycling, the fabricated 80 × 80 × 2.5 mm3 LSC device achieved a record-high external optical efficiency of 9.6%, while still maintaining 71% average visible transmittance. This work proves the substantial potential of enhancing the efficiency of CD-based LSC devices from the perspective of light absorption.